A study of changes in retailing and office accommodation with specific reference to the effect on the central business district of Cape Town - Levitan, Tali (Stellenbosch : Stellenbosch University, 2012)
Study project (M.A. in Town and Regional Planning) -- University of Stellenbosch, 1995.